2017
DOI: 10.12691/ajnr-5-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Guidelines for Prevention of Immobilization Complications on Caregivers' Performance and Patients' Functional Condition

Abstract: Long immobilization periods lead to overall complication and have been associated with poor functional outcomes. The aim of this study was to evaluate the effect of educational guidelines for prevention of immobilization complications on caregivers' performance and patients' functional condition. Quazi experimental design was utilized for conducting the study. Two purposive samples of 45 immobilized patients and their caregivers from orthopedic wards in El demerdash hospital, Cairo, Egypt, were randomly divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Hosseinpoor et al examined the socio-demographic characteristics of the caregivers of elderly people in low and middle-income countries, where the rate of female caregivers was found higher [9]. It was claimed that when the caregiver is young, they will understand the training better and make it easier to perform tasks that require physical effort such as the carrying and repositioning of the patient [10]. The reason for the lack of a significant difference between age and knowledge scores in our study may be the high mean age.…”
Section: Discussionmentioning
confidence: 99%
“…Hosseinpoor et al examined the socio-demographic characteristics of the caregivers of elderly people in low and middle-income countries, where the rate of female caregivers was found higher [9]. It was claimed that when the caregiver is young, they will understand the training better and make it easier to perform tasks that require physical effort such as the carrying and repositioning of the patient [10]. The reason for the lack of a significant difference between age and knowledge scores in our study may be the high mean age.…”
Section: Discussionmentioning
confidence: 99%
“…Patient education is considered the most valuable tool to ensure proper cast maintenance, preventing potential complications and improve patient outcomes. Furthermore, results of previous studies conducted in Egypt revealed significance correlation between incidence of local complication of plaster cast and improper cast care (Eldosoky and Ahmad, 2016) [10] , also the study of (Mersal, 2014) [19] that conducted in Demerdash Hospital Cairo, Egypt, and founded that there was low level of knowledge and performance of casted patients and their caregivers about cast care and prevention of immobilization complications. Researchers found that many patients managed with orthopedic plaster casts in Minia University suffering from local complications as a result of knowledge and practice deficiency regarding self-care management while working in the orthopedic ward.…”
Section: Significance Of the Studymentioning
confidence: 94%
“…Orthopaedic care's duty is to provide standardised patient care based on evidence-based practise for traction patients by doing musculoskeletal examinations, assisting with traction, and administering prescription pain medication. Orthopedic nurses assist and educate patients on mobility, joint and bone health, and the development of care plans to avoid issues (Mersal, Mersal, & Hussein, 2017).…”
Section: Significance Of the Studymentioning
confidence: 99%